2021
DOI: 10.1007/978-3-030-86478-1_14
|View full text |Cite
|
Sign up to set email alerts
|

Large Branchiopods in Small Water Bodies: A Case Study of the Ramsar Site “Bardača Wetland” (NW Republic of Srpska, Bosnia and Herzegovina)

Abstract: Ramsar site "Bardača Wetland" has been on the list of wetlands of international importance since 2007. It is situated in the northern part of Bosnia and Herzegovina, at the territory of Republic of Srpska. This site has a wide range of water bodies with various hydrological regimes that support a diverse locally adapted flora and fauna. The investigations of the large branchiopods have been carried out since 2016. The existence of this evolutionary very old group of crustaceans has previously not been known fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 44 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…In the Collection of the Natural History Department of the Museum of Republic of Srpska in Banja Luka, there are five specimens of this species (of different ages), collected in the forest on Lake Sinjak and along the Matura River in March and April, as well as one model (cast) made according to the specimen caught along the Matura River in March (Gašić, 2012). During the last few years of our field research, a noticeable decline in the population numbers of the fire-bellied toad was recorded, most likely a consequence of the ever increasing degradation of aquatic habitats at the Ramsar site "Bardača Wetland", as recently indicated by Miličić et al (2022). According to the "Decree on Strictly Protected and Protected Wild Species" in the Republic of Srpska this species is listed under the category of protected wild species (Anonymous, 2020).…”
Section: Triturus Dobrogicus (Kiritzescu 1903) -Danube Crested Newtmentioning
confidence: 94%
See 3 more Smart Citations
“…In the Collection of the Natural History Department of the Museum of Republic of Srpska in Banja Luka, there are five specimens of this species (of different ages), collected in the forest on Lake Sinjak and along the Matura River in March and April, as well as one model (cast) made according to the specimen caught along the Matura River in March (Gašić, 2012). During the last few years of our field research, a noticeable decline in the population numbers of the fire-bellied toad was recorded, most likely a consequence of the ever increasing degradation of aquatic habitats at the Ramsar site "Bardača Wetland", as recently indicated by Miličić et al (2022). According to the "Decree on Strictly Protected and Protected Wild Species" in the Republic of Srpska this species is listed under the category of protected wild species (Anonymous, 2020).…”
Section: Triturus Dobrogicus (Kiritzescu 1903) -Danube Crested Newtmentioning
confidence: 94%
“…The total number of individuals recorded during our field studies in the area of the settlements Bajinci and Bardača included about 20 adults and several larvae. Radević (2007) and Miličić et al (2022) previously reported presence of the Danube crested newt within the boundaries of the Ramsar site "Bardača Wetland". According to the "Decree on Strictly Protected and Protected Wild Species" in the Republic of Srpska this species is listed under the category of strictly protected wild species (Anonymous, 2020).…”
Section: Triturus Dobrogicus (Kiritzescu 1903) -Danube Crested Newtmentioning
confidence: 96%
See 2 more Smart Citations